Penatalaksanaan Skabies Melalui Pendekatan Kedokteran Keluarga di Wilayah Kerja Puskesmas Satelit - Niken Rahmatia; Tutik Ernawati (MAJORITY, 2020)
The high prevalence of scabies can be caused by poverty, low levels of education, poor hygiene, availability of clean water and density of residents. Diagnosis and treatment are carried out with a holistic and comprehensive family medicine approach. Primary data were obtained through history taking, physical examination and home visits, and secondary data from the patient's medical records. Patient's case a 51-year-old has suffered from scabies (ICD 10 - B86) that has recurred three months ago, but the patient still has a functional degree of 1 in carrying out daily activities. Internal factors in patients are poor personal hygiene, towels and bed linen do not wash regularly even though it has been used other than by family members, as well as curative treatment patterns. External factors in patients are low family income (ICD10-Z59.6), lack of home lighting and ventilation, densely populated home environments, lack of cleanliness in the home environment, and low patient and family knowledge about scabies. The holistic and comprehensive eradication approach uses a family medicine approach in the form of education about the causes, transmission, treatment and prevention of diseases. Scabies disease is difficult to eradicate if it is not accompanied by changes in clean and healthy lifestyle.